ASEAN Defense Diplomacy: Navigating US Tariffs and South China Sea Tensions - Saputra, Darma Eka; Perwita, Anak Agung Banyu; Hendarwoto, Yermia (Darul Yasin Al Sys, 2025)
This paper examines the evolution of ASEAN defense diplomacy in response to two major geopolitical challenges: the 2018 U.S.–China trade war and China’s increasing assertiveness in the South China Sea, with a specific focus on the Scarborough Shoal standoff. Utilizing a qualitative research approach, the study analyzes ASEAN’s institutional frameworks namely the ASEAN Defense Ministers' Meeting (ADMM), ADMM-Plus, and the ASEAN Regional Forum (ARF) to explore how defense diplomacy functions alongside economic strategies. The findings suggest that ASEAN’s defense diplomacy serves a stabilizing role by fostering regional unity, facilitating strategic hedging, and sustaining military communication channels amid escalating trade and maritime tensions. The study argues that ASEAN’s dual engagement with both the U.S. and China, despite the limitations of consensus-based diplomacy, enables the bloc to avoid alignment traps and enhances its collective resilience against external coercion. Ultimately, ASEAN defense diplomacy, though institutionally constrained, proves to be a vital instrument for maintaining strategic balance, upholding regional stability, and reinforcing the rules-based international order.